Maturation of induced pluripotent stem cell derived hepatocytes by 3D-culture. - Richard L Gieseck; Nicholas R F Hannan; Roque Bort; Neil A Hanley; Rosemary A L Drake; Grant W W Cameron; Thomas A Wynn; Ludovic Vallier (PLoS ONE)
Induced pluripotent stem cell derived hepatocytes (IPSC-Heps) have the potential to reduce the demand for a dwindling number of primary cells used in applications ranging from therapeutic cell infusions to in vitro toxicology studies. However, current differentiation protocols and culture methods produce cells with reduced functionality and fetal-like properties compared to adult hepatocytes. We report a culture method for the maturation of IPSC-Heps using 3-Dimensional (3D) collagen matrices compatible with high throughput screening. This culture method significantly increases functional maturation of IPSC-Heps towards an adult phenotype when compared to conventional 2D systems. Additionally, this approach spontaneously results in the presence of polarized structures necessary for drug metabolism and improves functional longevity to over 75 days. Overall, this research reveals a method to shift the phenotype of existing IPSC-Heps towards primary adult hepatocytes allowing such cells to be a more relevant replacement for the current primary standard.